Energy Security: Shaping the Consumer Decision Making Process in Emerging Economies - Loper, Taran; Crittenden, Victoria L. (Organizations and Markets in Emerging Economies, 2017)
Energy security is a universal concern among all countries, with all nations struggling for a sustainable solution. Solar technologies are a particularly beneficial utility for emerging economies due to both geography and affordability. Solar Photovoltaics (PV) is one of the highest potential growth markets in emerging economies due to the ability for small-scale systems to be placed on residential rooftops. Distribution of PV to individual homeowners is a new buying and selling process for what has traditionally been a business-to-business marketplace. Because the consumer market is at an infant stage in emerging economies, the messages that PV companies send to consumers will ultimately shape consumer perception about renewable energy. Through content analysis of websites from 12 companies in two of the BRICS markets, this research explores the similarities and differences with regard to consumer-facing messages among companies of various sizes in the two markets.